Chemotherapy and drug resistance in luminous bacteria from penaeid shrimp hatchery - Abraham, T Jawahar; Palaniappan, R (Indian Journal of Fisheries, 2011)
In-vitro activities of chloramphenicol, ciprofloxacin, nalidixic acid and oxytetracyclineagainst antibiotic-sensitive luminous Vibrio harveyi, V.orientalis andV.splendidus1 from penaeid shrimp hatchery were evaluated. The antibioticresistance rates for V.harveyi, V.orientalis and V.splendidus to chloramphenicol(1.92x10-10-9.38x10-8) and ciprofloxacin (1.92x10-10-2.45x10-9) were very lowat 5 and 10 times of their respective minimal inhibitory concentration (MIC)than at 2 times the MIC. The resistance rates for luminous bacteria to nalidixicacid (4.02x10-9-1.45x10-2) and oxytetracycline (1.92x10-10-3.95x10-2) were foundto be higher than chloramphenicol and ciprofloxacin. Although ciprofloxacinwas effective in terms of MIC and induction of low level of resistant isolates,chloramphenicol was more active in its ability to control antibiotic-sensitiveluminous bacteria.